2017
DOI: 10.1007/s00464-017-5432-1
|View full text |Cite
|
Sign up to set email alerts
|

Repair of symptomatic paraesophageal hernias in elderly (>70 years) patients results in sustained quality of life at 5 years and beyond

Abstract: In elderly patients with symptomatic PEH undergoing surgical repair more than 5 years ago, there was sustained improvement in quality of life. This justifies surgical repair of symptomatic PEH in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…[ 23 28 39 46 55 ] Two studies found that there was no significant increase in post-surgical QoL. [ 56 57 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 23 28 39 46 55 ] Two studies found that there was no significant increase in post-surgical QoL. [ 56 57 ]…”
Section: Resultsmentioning
confidence: 99%
“…Five studies[ 5 24 25 30 57 ] looked at QoL after repair of GHH with focus on the age demographic of patients [ Table 4 ]. Parker et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a paucity of high-level evidence literature on elective PEH repair in elderly patients. A few studies defined elderly as > 70 years [3, 8, 9] or analyzed a very small group of elderly patients [5, 7, 10, 16], making comparison with our data difficult. Only one study evaluating elective PEH repair in 313 patients ≥ 80 years revealed a significant increase in minor morbidity (8.3% vs. 3.5%, p < 0.001), and a trend towards slightly higher mortality (1% vs. 0.4%, p = 0.16) and major morbidity (5.8% vs. 3.7%, p = 0.083) for patients ≥ 80 years [11].…”
Section: Discussionmentioning
confidence: 99%